Buchwald's atlas of metabolic & bariatric surgical techniques and procedures - Buchwald, Henry (Elsevier/Saunders, 2012)
Buchwald's Atlas of Metabolic & Bariatric Surgical Techniques and Procedures, by leading authority Henry Buchwald, MD, PhD, is the first pictorial atlas that demonstrates today's full range of open and laparoscopic bariatric procedures, as well as concurrent surgeries such as hernia repair and tubal ligation. Hundreds of high-quality photographs and illustrations show you how to achieve the best outcomes and manage any complications that may arise. You'll find coverage of such hot new approaches as laparoscopic electrode placement, alternative open electrode placement, laparoscopic vagal pacing, and alternative open vagal pacing. At www.expertconsult.com you can reference the complete text and illustrations from any computer or mobile device. See how to perform today's full range of open and laparoscopic techniques, as well as concurrent surgeries such as hernia repair and tubal ligation, by viewing hundreds of step-by-step photographs and illustrations. Master hot new procedures such as laparoscopic electrode placement, alternative open electrode placement, laparoscopic vagal pacing, and alternative open vagal pacing. Obtain the best results and avoid complications with expert tips and recommendations from Dr. Henry Buchwald, who has chaired or presided over the Surgical Council of the American College of Nutrition, the Central Surgical Association, the American Society for Bariatric Surgery, and other leading organizations. Reference the complete text and illustrations from any computer or mobile device at www.expertconsult.com.